2018
DOI: 10.1002/jcp.26342
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP3 deposited in the human umbilical cord mesenchymal stem cell‐secreted extracellular matrix promotes bone formation

Abstract: The extracellular matrix (ECM) contains rich biological cues for cell recruitment, proliferationm, and even differentiation. The osteoinductive potential of scaffolds could be enhanced through human bone marrow mesenchymal stem cell (hBMSC) directly depositing ECM on surface of scaffolds. However, the role and mechanism of human umbilical cord mesenchymal stem cells (hUCMSC)‐secreted ECM in bone formation remain unknown. We tested the osteoinductive properties of a hUCMSC‐secreted ECM construct (hUCMSC‐ECM) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…BM‐ECM tissue culture substrates have been previously investigated 28,42,43 and found to be an improved cell culture environment to preserve the stem‐ness of cultured cells by providing a cell‐free extracellular matrix compared to regular tissue culture plates containing one or a select few extracted and purified ECM proteins 44 . Comparative studies evaluating cell proliferation rate, cell size, and cell surface markers of MSCs cultured on the BM‐ECM matrix versus other commercially available coated dishes exhibited more rapid proliferation, smaller cell size, and higher expression of certain stem cells markers in BM‐ECM tissue cultured plates than in the other products 19,28,42,43,45 . Having been produced from bone marrow MSCs rather than other standard matrix producing cells (fibroblasts), 46,47 BM‐ECM tissue culture substrates can be considered to be the more biologically niche‐relevant ECM for inducing osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BM‐ECM tissue culture substrates have been previously investigated 28,42,43 and found to be an improved cell culture environment to preserve the stem‐ness of cultured cells by providing a cell‐free extracellular matrix compared to regular tissue culture plates containing one or a select few extracted and purified ECM proteins 44 . Comparative studies evaluating cell proliferation rate, cell size, and cell surface markers of MSCs cultured on the BM‐ECM matrix versus other commercially available coated dishes exhibited more rapid proliferation, smaller cell size, and higher expression of certain stem cells markers in BM‐ECM tissue cultured plates than in the other products 19,28,42,43,45 . Having been produced from bone marrow MSCs rather than other standard matrix producing cells (fibroblasts), 46,47 BM‐ECM tissue culture substrates can be considered to be the more biologically niche‐relevant ECM for inducing osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…39 As shown in Figure 5b, smaller cell size, and higher expression of certain stem cells markers in BM-ECM tissue cultured plates than in the other products. 19,28,42,43,45 Having been produced from bone marrow MSCs rather than other standard matrix producing cells (fibroblasts), 46,47 BM-ECM tissue culture substrates can be considered to be the more biologically nicherelevant ECM for inducing osteogenesis.…”
Section: Radiography and μCt Analysismentioning
confidence: 99%
“…65 Meanwhile, IGFBP3 is an important MSC homing molecule in bone regeneration in an IGFBP3-dependent mechanism. 66 HSPA13 is a member of the Hsp70 family of ATPase heat-shock proteins, which have been previously implicated in prion propagation. 67 These evidences demonstrated that IGF2 could enhance the functional protein secretion in microenvironment to promote cell proliferation and differentiation abilities of SCAPs.…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP3 is the most abundant insulin‐like growth factor receptor in the serum and binds the majority of insulin‐like growth factors 65. Meanwhile, IGFBP3 is an important MSC homing molecule in bone regeneration in an IGFBP3‐dependent mechanism 66. HSPA13 is a member of the Hsp70 family of ATPase heat‐shock proteins, which have been previously implicated in prion propagation 67.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium nodules are produced by osteoblasts during the mineralization of the extracellular matrix. 37 Thus, ARS staining was performed to investigate the effects of compound 17 on osteogenic differentiation and mineralization. The results showed that the mineralization area of the plate was promoted in the compound 17-treated groups compared to the control groups ( Figure 6A).…”
Section: Compound 17 Promoted Osteoblast Differentiation and Mineralimentioning
confidence: 99%